Hambatan Komunikasi dan Penyelesaian Konflik Dalam Negosiasi Bisnis - Hermika Pinem; Monika Ayu Lumbantoruan; Resy Tamara; Danny Ajar Baskoro; Lenti Susanna Saragih (Student Scientific Creativity Journal, 2024)
Modern business, whether in trade of goods or services, is experiencing rapid growth that contributes to the global economy. However, globalization and technological advancements have brought challenges in communication and conflict resolution, especially in cross-cultural negotiations. This research aims to investigate communication barriers and conflict resolution strategies in the context of multicultural business negotiations, focusing on factors influencing intercultural communication and effective approaches to conflict resolution. A literature review approach is employed in this study. Data is collected from various related literature, including books, scientific journals, and articles discussing communication barriers and conflict resolution in business from 2015 to 2024. The data is critically analyzed to identify the relationship between communication barriers and conflict resolution in business negotiations. The research results indicate that language differences, communication styles, social norms, business ethics, and perceptions of time are major barriers in intercultural communication that can disrupt business negotiations. These barriers often lead to misunderstandings and conflicts that can damage business relationships. Additionally, interest-based approaches and Pancasila-based deliberation are identified as effective conflict resolution strategies, emphasizing the values of democracy, kinship, and mutual cooperation.